ABOUT STUDENTS' READYNESS FOR SELF-LEARNING FOREIGN LANGUAGE IN THE CONDITIONS OF THE GROUP (Pedagogy of Higher and Secondary Education, 2022)
This article is devoted to the questions of investigation of pupils’ self-work which takes place at the conditions of its Wjnnization in group. Before its realization different types of learning actions take place. The necessity of high motivation is proved, different components of readiness to the fulfillment of self-work are investigated.